Pengaruh Penerapan Profitabilas Dan Economic Value Added Terhadap Return Saham Pada Perusahaan Food and Beverages Yang Terdaftar di Bursa Efek Indonesia Tahun 2015-2019 - Gabriella Sinabang; T. Alvi Syahri Mahzura; Muhammad Akbar Siregar (Jurnal Ilmiah Akuntansi Keuangan dan Bisnis (JIKABI), 2022)
This study aims to determine whether Return on equity, Earning per share and Economic value added partially and simultaneously affect Stock Returns in Food and Beveragess companies listed on the Indonesia Stock Exchange. The indendent variables used in this study are Return on equity, Earning per share and Economic value added, while the dependent variable is Stock Return. The population in this study were 26 food and beverage companies listed on the Indonesia Stock Exchange for the period 2015-2019. In this study, researchers took samples using purposive sampling technique which aims to determine the sampling criteria by making special characteristics that match the research objectives, so that from 26 companies to 14 companies that become the criteria in this study. The type of data in this research is quantitative data. The data source used is secondary data. The data analysis technique used is multiple regression analysis and then hypothesis testing using SPSS. The results showed that partially Return On Equity (X1) have a positive and significant effect on Stock Returns, while Earning Per Share (X2) have a positive and significant effect on Stock Returns, and Econimic Value Added (X3) have a positive and significant effect on Stock Returns, and simultaneously Returns. on equity, Earning per share and Economic value added have a positive and significant effect on stock returns.